Comparative Phytochemical and Inorganic Ion Analysis of Vellai Vengaya Kulligai: A Siddha Herbo-Mineral Preparation using two ingredient variants - Prasad, V.M.; Sathiyaseelan, V.; Velauthamurty, K. (Postgraduate Institute of Indigenous Medicine, University of Colombo, 2025)
With the increasing global recognition of traditional and indigenous medical systems, there is a growing emphasis on the need to standardize and scientifically evaluate the quality of traditional formulations. Vellai Vengaya Kuligai (VVK) is a herbo-mineral formulation in Siddha medicine traditionally used for managing conditions such as Mantham (indigestion), Kazhichal (diarrhea), and Vaayu (pain). Comprising 23 ingredients primarily herbal, with detoxified borax and rock salt VVK holds a prominent place in Siddha therapeutics. Although the term “Vellai Vengayam” suggests the use of white onion, classical Siddha literature indicates the substitution of garlic (Ulli) in its preparation. This study investigates the phytochemical profile of VVK prepared using two methods, one with white onion and the other with garlic and compares their constituents. While white onion is known to contain alkaloids, tannins, phenols, and terpenes, the corresponding VVK tablets were found to have alkaloids, flavonoids, saponins, and terpenes. In contrast, garlic contains alkaloids, phenols, tannins, and saponins, and the tablets prepared with garlic exhibited a broader spectrum, including alkaloids, flavonoids, phenols, tannins, saponins, terpenes, and trace inorganic elements such as iron, nickel, and nitrate. The enhanced phytochemical content observed in the garlic-based tablets suggests greater therapeutic potential as described in classical Siddha texts. This preliminary comparative analysis provides a scientific foundation for understanding the compositional differences arising from variation in preparation methods
Keywords: Herbo-mineral; Phytochemical; Siddha; Vellai vankaya kuligai